2020
DOI: 10.1017/s1463423620000274
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ knowledge of leg ulcer treatment in primary healthcare: an interview study

Abstract: Aim: To describe general practitioners’ (GPs’) knowledge and the development of their knowledge regarding leg ulcer treatment when treating patients with leg ulceration at primary healthcare centers. Background: Earlier research regarding GPs’ knowledge of leg ulcer treatment in a primary healthcare context has focused primarily on the assessment of wounds and knowledge of wound care products. Less is known about GPs’ understandings of their own knowledge and knowledge development regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…10 Woo and Sears 11 also described a lack of knowledge in providing appropriate and consistent treatments for persons with MLU in a sample of 436 wound care clinicians, of whom 68.8% were nurses. Friman et al 12 suggested that general practitioners also have insufficient knowledge to manage LUs efficiently in primary healthcare settings. It is important that nurses improve their skills and knowledge to offer the best wound care for persons living with an LU.…”
Section: Introductionmentioning
confidence: 99%
“…Author: Kirsi Isoherranen ulcer, if there are no contraindications. It is widely recognised that GPs might not have sufficient knowledge of leg ulcer assessment and treatment (11). Likewise, nurses and allied health professionals treating lower leg ulcers should be aware of the differential diagnostics and referral pathways so that the individual does not have to self-manage too long, and adequate referrals are done.…”
mentioning
confidence: 99%